2008
DOI: 10.1007/s12272-001-2129-7
|View full text |Cite
|
Sign up to set email alerts
|

Tectorigenin inhibits IFN-γ/LPS-induced inflammatory responses in murine macrophage RAW 264.7 cells

Abstract: Tectorigenin (Tg) and tectoridin (Td) are the major compounds isolated from the rhizomes of iridaceous plant Belamcanda chinensis which is well known as a chinese traditional medicine for the treatment of inflammatory diseases. In this study we investigated whether tectorigenin and tectoridin can be applied to the suppression of interferon-gamma and lipopolysaccharide (IFN-gamma/LPS)-induced inflammatory responses in macrophages. Anti-inflammatory activities of tectorigenin and tectoridin were compared with ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 60 publications
(57 reference statements)
2
63
0
1
Order By: Relevance
“…To examine the potential of PT as a modulator of inflammation process, we used Raw 264.7 cell line, which was established from mouse peritoneal macrophage derived tumor cells. This cell line is often used in inflammatory and metabolic studies (Pan et al, 2008;Oh et al, 2010). Our study showed that the pretreatment of PT extracts inhibited NO and COX-2 production from LPS- Fig.…”
Section: Discussionmentioning
confidence: 60%
“…To examine the potential of PT as a modulator of inflammation process, we used Raw 264.7 cell line, which was established from mouse peritoneal macrophage derived tumor cells. This cell line is often used in inflammatory and metabolic studies (Pan et al, 2008;Oh et al, 2010). Our study showed that the pretreatment of PT extracts inhibited NO and COX-2 production from LPS- Fig.…”
Section: Discussionmentioning
confidence: 60%
“…The dotted arrow represents bioactive compounds isolated from C. odorata that may be involved in the wound healing process individually or in combination, whereas the bold arrow indicates the definite involvement of scutellarein tetramethyl ether, stigmasterol and C1 in the process Veterinarni Medicina, 62, 2017(10): 565-578 doi: 10.17221/161/2016 Inflammation is a response to any tissue injury in the body caused by infection, trauma, chemicals, heat or unrecognised particles (Kim et al 2006). Inflammation, which constitutes a part of the acute response, results in a coordinated influx of neutrophils to the wound site which, through their characteristic "respiratory burst" activity, produce free radicals (Pan et al 2008). Topical application of compounds with free radical-scavenging properties in patients have shown to considerably improve wound healing and protect tissues from oxidative damage (Pisutthanan et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Production of NO was assayed by measuring the levels of nitrite, as described in previous report [15]. Briefly, the test samples were treated as described in cell viability assay, and then the culture supernatant was collected at the end of culture for nitrite assay, which was used as a measurement of NO production.…”
Section: No Measurementmentioning
confidence: 99%
“…Western blot analysis was performed as described in previous report [15]. Raw 264.7 cells were cultured in the presence of LPS or in combination with each samples in a 6-well plate (1×10 6 cells/well).…”
Section: Western Blot Analysismentioning
confidence: 99%